Biomolecular condensation-mediated actin remodeling in plant innate immunity - Ma, Zhiming (Nanyang Technological University, 2021)
Upon bacterial invasion, the plant host acutely remodels the actin cytoskeleton to coordinate defense mechanisms. However, the molecular mechanisms by which plant triggers rapid actin remodeling remain enigmatic. In my PhD study, we have found that plant actin nucleation factor, type-I formin, serves as the molecular sensor that responds to bacterial virulence factors for actin remodeling during host immune signalling. Two types of virulence factors of Xanthomonas campestris pv. campestris (Xcc), diffusible signal factor (DSF), and pathogen-associated molecular pattern (PAMP), flagellin (flg22), regulate actin assembly through oppositely tuning the type-I formin nano-clustering on the plasma membrane (PM). The formin nano-clustering and nucleation activity depend highly on the mechanical regulation by the cell wall-PM-actin cytoskeleton continuum during both DSF and PAMP signalling. Specifically, DSF attenuates formin nano-clustering and causes reduced actin assembly by perturbing the integrity of cell wall. While PAMPs trigger the nano-clustering of formin in a PM nanodomain assembly factor Remorin-dependent manner. Together, our results have unravelled a central molecular mechanism for rapid actin remodeling during plant-bacteria interactions, in which bacterial signalling molecules finetune plant type-I formin condensation in a host mechanical structure-dependent manner.